The Influence of Corporate Social Responsibility (CSR) on Company Performance and Company Reputation as a Mediation Variable (Study on Companies in the Sri-Kehati Index Year 2017- 2021) - Yumna Syaza Kani Putri; Wirmie Eka Putra; Susfa Yetti (Journal of Accounting and Finance Management, 2023)
This research was carried out to determine the relationship between the influence of Corporate Social Responsibility (CSR) on company performance and company reputation as a mediating variable in the Sri-Kehati Index Company in 2017-2021 using smartpls as a tool for processing data. The results of data processing found that Corporate Reputation had a significant positive effect on Company Performance, Corporate Social Responsibility (CSR) had a significant negative effect on Company Reputation, then Corporate Social Responsibility (CSR) had an insignificant negative effect on Company Performance, and finally Corporate Reputation had a significant negative effect. As mediation in the relationship between Corporate Social Responsibility (CSR) and Performance Company.